Analysis of motor behavior in piano performance from the mixed methods approach - Santisteban, Isabel E.; Anguera, M. Teresa; Granda-Vera, Juan; Pastrana-Brincones, José Luis (Frontiers in Psychology, 2024)
The focus of this study centers on the extraction, analysis, and interpretation of the motor behavior of advanced level pianists using observational methodology, itself framed within the field of mixed methods, paying particular attention to those aspects that characterize the pressed and struck touch. The aim of this research was to analyze the motor interactions of activation or inhibition associated with the production of a type of touch in the movements of the right upper limb of the participating pianists. An ad hoc observational instrument was built that was incorporated into the software Lince Plus for data recording and coding. Data reliability was guaranteed applying Cohen’s Kappa coefficient, and an analysis of polar coordinates was carried out to identify the motor interactions involved in piano playing. This research represents an innovative perspective of the study of piano-playing movement via the direct and perceptible observation of the pianist’s motor behavior in an everyday context. This model allows us to describe and analyze piano touch for its application in the field of piano performance and teaching. Observational methodology is distinguished by its low degree of internal control, which makes it possible to scientifically study the spontaneous behavior of pianists in their natural environment. The results of this study have provided significant information about the interaction of motor functions linked to two types of touch, such as those that occur in the sliding finger movement over the key in the pressed touch or the lifting finger movement above the key in the struck touch, obtaining clearly identified patterns of piano touch motor behavior.